Locating a Sense of Place on Social Media: A focus on Aotearoa New Zealand - Sidney Wong (13714252) (2025)
Wong, S. (2025, July). Locating a Sense of Place on Social Media: A focus on Aotearoa New Zealand. Presentation for the Deputy Vice Chancellor R&I Visit to the Geospatial Research Institute, Jul 23, University of Canterbury.